Hubungan Antara Kelompok Referensi dengan Perilaku Konsumtif - Anggadini, Tian Kusuma, Dra. Zahrotul Uyun, M.Si (2015)
Students mostly live boarding should be able to manage finance and simple life, but now students often imitate reference group in everyday behavior with frequent trips to the mall, have the goods the same function more than one, and love goods branded of foreign. This research purposes (1) Knowing the relationship between the reference group with the consumer behavior on the students of the Psychology Faculty Year 2013 Muhammadiyah University of Surakarta. (2) Determine consumer behavior level of students of Psychology Faculty Year 2013 Muhammadiyah University of Surakarta (3) Knowing reference group level of students of Psychology Faculty Year 2013 Muhammadiyah University of Surakarta. (4) To analyze of reference group role on consumer's behavior of students of Psychology Faculty Year 2013 Muhammadiyah University of Surakarta. Hypothesis this study is positive correlation between the reference group with the consumer's behavior of students Psychology Faculty Muhammadiyah University of Surakarta. Meaning that reference group is higher so consumer's behavior of students is higher too, conversely reference group is lower so consumer's behavior of students is lower too. This research was conducted in psychology students Year 2013 with total 77 samples of two classes. Variable in this study is consumptive's behavior and reference group. Collection data tools in this study are instruments scale and questionnaires. Measuring instruments used in this study are a reference group scale and consumer's behavior scales; each consists of 36 questions 16 questions favorable and 16 questions unfavorable. Research test is validity and reliability, data analysis methods including normality, linearity and hypothesis test using product moment correlation. The results showed: (1) there is a positive relationship between the reference group with the consumer's behavior based on results of the product moment correlation 0.426 p = 0.000 (2) variable reference group had a mean empirical (RE) = 91.14, and the mean hypothetical (RH) of 90 which means that the reference group on themselves is high. (3) The behavior of the average consumer empirical (RE) 88.84 and a mean of 90 which means the hypothetical consumer's behavior subject are high. (4) Effective contribution amounting to 0.426 so that students of consumer behavior is influenced by the reference group of 42.6% while the remaining 57.4% is influenced by other factors. Keywords: reference groups, consumer's behavior, psychology students.